Hypoxic Conditioning in Rehabilitation and Secondary Prevention Programs in Cardiac Patients with Multimorbidity: a Review - Nadezhda P. Lyamina; Galina K. Spirina; Oleg S. Glazachev (Вестник восстановительной медицины)
INTORDUCTION. Patients with multiple chronic diseases are at higher risk of premature death, hospitalization, longer hospital stays, and reduced health-related quality of life compared to patients with a single disease. On the other hand, the presence of comorbid conditions limits the enrolment of traditional exercise-based cardiac rehabilitation programs. It is predicted that as life expectancy increases, the level of multimorbidity will increase, making it even more important to find new additional methods and technologies for the rehabilitation of cardiac patients with comorbidities. AIM. To analyze the data from the current publications or to define the validity and effectiveness of using different hypoxic conditioning regimens in cardiac patients with concomitant chronic pathology (arterial hypertension, obesity, diabetes mellitus, and chronic bronchopulmonary diseases) as well as in multimorbid elderly patients. MATERIAL AND METHODS. The search for relevant papers was carried out using the Medline, e-library, and Web of Science Core Collection databases, as well as the following keywords: “hypoxic conditioning”, “hypoxic training”, “hypoxic therapy”, “interval hypoxic therapy”, “intermittent hypoxia”, “hypoxic conditioning”, “interval hypoxia training”, and “hypoxic exposure”. The analysis included publications regarding the use of the hypoxic conditioning method in cardiac and elderly patients with multimorbid pathology, as well as publications on the use of the method in the rehabilitation of patients with certain nosologies to identify potential mechanisms in correcting bronchopulmonary violations and lipid and carbohydrate metabolism disorders. The last search date was April 05, 2022. RESULTS. Most of the analyzed studies proved that the hypoxic conditioning technology in passive interval exposure regimes is an effective method for non-pharmacological correction of cardiometabolic risks in cardiac patients with multimorbid pathology and can increase exercise tolerance, optimize hemodynamic parameters (HR, SBP and DBP), reduce the manifestations of bronchial obstruction and respiratory failure, and improve cognitive function and metabolic indicators. Personalized physical activity doses in oxygen-depleted ambient air appear to be promising, but require additional studies to establish optimal application protocols. CONCLUSION. The data presented may recommend hypoxic conditioning technologies for wider implementation in cardiac rehabilitation programs for patients with multimorbid pathologies.